1984
DOI: 10.1051/jphyslet:0198400450210101500
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of the Laplacian and random matrix theories

Abstract: 2014 Nous étudions les propriétés de fluctuation des valeurs propres du Laplacien à deux dimensions avec des conditions aux limites de Dirichlet sur un stade. Elles sont consistantes avec les fluctuations des valeurs propres de matrices aléatoires (GOE). Nous faisons la conjecture que ceci est vrai en général, pourvu que la frontière soit telle que le mouvement d'une particule libre réfléchie élastiquement par la frontière (billard) soit un mouvement très chaotique. Abstract. 2014 We investigate the fluctuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 11 publications
2
81
1
1
Order By: Relevance
“…The Bohigas-Giannoni-Schmit conjecture [27] and later works suggest that for a chaotic system, it is appropriate to apply RMT arguments to understand its statistical behavior. Here, as mentioned already, one has to add the caveat -as long as ǫ is weak enough that C(ǫ; t) decays on a much longer time scale than the logtime.…”
Section: The Fidelitymentioning
confidence: 99%
“…The Bohigas-Giannoni-Schmit conjecture [27] and later works suggest that for a chaotic system, it is appropriate to apply RMT arguments to understand its statistical behavior. Here, as mentioned already, one has to add the caveat -as long as ǫ is weak enough that C(ǫ; t) decays on a much longer time scale than the logtime.…”
Section: The Fidelitymentioning
confidence: 99%
“…[18][19][20][21][22] This result allows for a nonparametric description of the spacings distribution, i.e., a description that does not depend on the underlying random parameters. The degree of randomness can be quantified by the statistical overlap factor, which is defined as 34 …”
Section: B Spacing Statistics and The Goementioning
confidence: 99%
“…For the point load, the variance of the modal force is directly obtained from Eqs. (9) and (21). For the line load, Eqs.…”
Section: A Single Thin Plate Point and Line Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Dyson showed that the statistical predictions of RMT could be reproduced within a Brownian motion model, where Brownian motion of the energy levels results from a stochastic perturbation of some initial, possibly nonrandom, Hamiltonian [1]. Bohigas, Giannoni, and Schmit argued that the same universal behavior of the spectrum occurs generically even in single-particle systems, as long as the underlying classical dynamics is chaotic [2].…”
Section: Introductionmentioning
confidence: 99%